1993
DOI: 10.1142/s0217751x93000102
|View full text |Cite
|
Sign up to set email alerts
|

N=2 W Supergravity

Abstract: We quantize the classical gauge theory of N = 2 Woo supergravity and show how the underlying N = 2 super-woo algebra gets deformed into an N = 2 super-Woo algebra. Both algebras contain the N = 2 super-Virasoro algebra as a subalgebra. We discuss how one can extract from these results information about quantum N = 2 WN supergravity theories containing a finite number of higher-spin symmetries with superspin s ≤ N. As an example we discuss the case of quantum N = 2 W3 supergravity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1993
1993
1993
1993

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 55 publications
(167 reference statements)
0
6
0
Order By: Relevance
“…This fact has been noticed in ref. [8] where it has been also observed that, by adjusting the parameter value, one can cancel the central charge in the spin 1 sector of w 1+∞ and so make the modified currents obey the centreless w 1+∞ . As it is seen from the OPE's (3.3) and (3.14), in our notation this cancellation occurs at…”
Section: Two Scalar Fields Realization Of W 1+∞mentioning
confidence: 96%
See 2 more Smart Citations
“…This fact has been noticed in ref. [8] where it has been also observed that, by adjusting the parameter value, one can cancel the central charge in the spin 1 sector of w 1+∞ and so make the modified currents obey the centreless w 1+∞ . As it is seen from the OPE's (3.3) and (3.14), in our notation this cancellation occurs at…”
Section: Two Scalar Fields Realization Of W 1+∞mentioning
confidence: 96%
“…4.1 and demonstrate that the two-field realizations of ref. [3,8] can be derived in this way. Secondly, one may still deal with the same w 1+∞ as in ref.…”
Section: Two Scalar Fields Realization Of W 1+∞mentioning
confidence: 99%
See 1 more Smart Citation
“…The OPE's where s and/or I equals 1/2 can be found in ref. [25]. By definition, the symbol s~2is equal to zero fors even and 1 for s odd.…”
Section: Other W-algebrasmentioning
confidence: 99%
“…Its generic expression is given by [24,t;~)(12)S+t+1/22(S+t)I, + regular part. (30)The structure functions J~(D1,D2A) are polynomials in the supercovariant derivatives of degree 2u -1, whose explicit form is given in ref [25]…”
mentioning
confidence: 99%